Studies on Synthesis of Aldimines: Part-III. Synthesis, Spectral Characterization and Bioactivity of Salicylaldimines - Patil, C. J.; Patil, Manisha C.; Patil, Mrunmayee C. (Recent Research in Science and Technology, 2020)
Compounds containing >C=N- (azomethine) were prepared from Salicylaldehyde with Aniline derivatives by conventional chemical synthesis method. The products are tested in process and the completion of reaction product formation was ascertained by TLC. The final products were characterized by physical viz. m.p., analytical viz. TLC, Instrumental viz. UV-Vis and FTIR spectral techniques. Results showed that all the marked activity coefficients(biopotential) for the studied compounds are less than the standard drug, Ketoconazole.